The D-Bar Method for Diffuse Optical Tomography: A Computational Study. Issue 2 (3rd April 2017) - Tamminen, J.; Tarvainen, T.; Siltanen, S.
ABSTRACT: The D-bar method at negative energy is numerically implemented. Using the method, we are able to numerically reconstruct potentials and investigate exceptional points at negative energy. Subsequently, applying the method to diffuse optical tomography, a new way of reconstructing the diffusion coefficient from the associated Complex Geometrics Optics solution is suggested and numerically validated.